ANALYZING CUSTOMER PERCEPTION OF JAPANESE DESSERT SHOP IN MANADO (CASE STUDY: SUMOBOO AND SUMIKKO) - Gefilem, Desiree .; Lapian, Joyce .; Pandowo, Merinda . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Japanese cuisine become trend in Indonesia and people are attracted to the flavor which surprisingly suit with Indonesian taste. One of the most popular Japanese dessert in Indonesia is Sumoboo which is a franchise shop. On the other hand, there is a local brand call Sumikko that only exist in Manado. This research aims to analyze the Customer Perception of Japanese Dessert Shop. The type of this research is descriptive with qualitative approach. The sample size of this research is 15 informants who are the customer of Sumoboo and Sumikko. The sampling method used in this research is purposive and snowball sampling by doing interview with the customer. The key findings regarding customer perception showed the top three consideration include: Quality, Value, and Financial Risk. In this case, people in Manado have a different perception toward Japanese Dessert. The results of Customer Perception show that percentage of perceive quality, perceive value and perceive risk attributs are important to the customer but not significant. This study was done with hope that it could contribute to the future researchers to examined the other attributs that affect customer perception, the business that similar with Sumoboo and Sumikko to increase the profit or advantages.Â Keywords: customer perception, perceive quality, perceive value, perceive risk, dessert shop.